Recent Advances in the Prediction of Subcellular Localization of Proteins and Related Topics - Nakai, Kenta; Wei, Leyi (Frontiers in Bioinformatics, 2022)
Prediction of subcellular localization of proteins from their amino acid sequences has a long history in bioinformatics and is still actively developing, incorporating the latest advances in machine learning and proteomics. Notably, deep learning-based methods for natural language processing have made great contributions. Here, we review recent advances in the field as well as its related fields, such as subcellular proteomics and the prediction/recognition of subcellular localization from image data.